Latissimus dorsi transfer or lower trapezius transfer: a treatment algorithm for irreparable posterosuperior rotator cuff tears muscles transfers in posterosuperior rotator cuff tears - Michael Kimmeyer, MD; Tilman Hees, MD; Laurens Allaart, MD; Rémi Nerot, MD; Arno Macken, MD; Geert-Alexander Buijze, MD, PhD, FEBHS; Laurent Lafosse, MD; Thibault Lafosse, MD (JSES International)
Background: Tendon transfers of the latissimus dorsi transfer (LDT) or the lower trapezius transfer (LTT) are treatment options for irreparable posterosuperior irreparable rotator cuff tears (PSIRCT). There is still no consensus on which type of tendon transfer is superior in the treatment of PSIRCT. Due to the differences in the anatomy and biomechanics, we hypothesize that there are different clinical situations in which either LDT or LTT should be preferred. The aim of this study was to evaluate the clinical and radiological outcomes of LDT and LTT in patients with PSIRCT to establish a clinical algorithm for the treatment decision. Materials and methods: This is a retrospective, single-center observational study. Included were patients who underwent arthroscopically assisted LDT (aaLDT) or arthroscopically assisted LTT (aaLTT) for PSIRCT. In all patients, range of motion (ROM), external rotation strength, visual analog scale of pain and subjective shoulder value were determined pre- and postoperatively. Constant–Murley score was evaluated at the final follow-up. The complication rate, failure of the tendon transfer, and revision rate were analyzed. Results: In total, 29 aaLDT (age 64 years, median follow-up time 45 months) and 8 aaLTT (age 54 years, median follow-up time 34 months) were included. Active ROM, visual analog scale and subjective shoulder value was significantly improved in both cohorts. At follow-up, the median Constant–Murley score was 73 (aaLDT) and 77 (aaLTT), respectively. The failure rate, including revision surgery, was 14% (aaLDT) and 13% (aaLTT), respectively. Low functional findings preoperatively were correlated to a lower functional outcome at follow-up in both groups. Painful loss of anterior elevation and loss of external rotation had no significant impact on functional outcomes in aaLDT. Conclusion: Following the treatment algorithm based on the clinical examination, clinical outcome parameters, active ROM and pain could be significantly improved. A good preoperative function was associated with a good clinical outcome in both transfers. A low failure and revision rate supports the good decision-making of the algorithm presented.